2021
DOI: 10.3992/jgb.16.4.45
|View full text |Cite
|
Sign up to set email alerts
|

Resale of Green Housing Compensates for Its Premium Pricing: An Empirical Study of China

Abstract: Green housing reduces resource consumption and protects the ecological environment. Sustainable buildings and construction have gained increasing attention in the last decade. Many empirical studies have confirmed that green housing imposes a price premium at the presale stage. The high price could be a concern that prevents homebuyers from purchasing green buildings. However, there is a lack of empirical evidence on whether the premium pricing could be compensated for by the resale price. To address this gap,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The resale price for redevelopment could compensate for the high investments from builders. For example, studies have found that the transaction prices of green buildings are 6% higher in the resale market [25].…”
Section: Energy Retrofitmentioning
confidence: 99%
“…The resale price for redevelopment could compensate for the high investments from builders. For example, studies have found that the transaction prices of green buildings are 6% higher in the resale market [25].…”
Section: Energy Retrofitmentioning
confidence: 99%